# Find the general solution of each of the following equations:sin x tan x – 1 = tan x – sin x

To Find: General solution.

Given: sin x tan x – 1 = tan x – sin x sin x(tan x + 1) = tan x + 1

So sin x = 1 = sin ( ) or tan x = -1 = tan( )

Formula used: sin = sin = n + (-1)n , n I and tan = tan = k , k I x = n + (-1)n or x = k where n, k I

So general solution is x = n + (-1)n or x = k where n, k, I

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Interactive Quiz on trigonometric identities & equations52 mins  Conditional Identities31 mins  Graphs of trigonometric ratios | Trigonometric Identities39 mins  Trigonometric Series45 mins  Trigonometric Functions - 0152 mins  Quiz on Graph of Trigonometric Ratios40 mins  Trigonometric Functions - 0568 mins  Trigonometric Functions - 0366 mins  Trigonometric Functions - 0658 mins  Interactive Quiz on trigonometric ratios & identities73 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 